2020
DOI: 10.1177/2192568220901694
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Accuracy of the AO Spine-TL Classification for Thoracolumbar Spine Fractures Using the AO Surgery Reference Mobile App

Abstract: Study Design: Cohort study. Objectives: This study aimed to evaluate the accuracy of the AO Surgery Reference mobile app in the diagnosis of thoracolumbar fractures of the spine according to the AO TL classification, and to discuss the usefulness of this app in the teaching and training of the resident physicians in orthopedics and traumatology area. Methods: The 24 residents of Orthopedic and Traumatology program assessed 20 cases of thoracolumbar fractures selected from the hospital database on 2 different o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They succeeded in showing that residents improved their ability to recognize and classify thoracolumbar spine fractures through app-usage. Therefore, they concluded that their findings reinforce the importance of mobile applications in medical education and clinical practice [ 26 ]. The results of both publications support our findings.…”
Section: Discussionmentioning
confidence: 89%
“…They succeeded in showing that residents improved their ability to recognize and classify thoracolumbar spine fractures through app-usage. Therefore, they concluded that their findings reinforce the importance of mobile applications in medical education and clinical practice [ 26 ]. The results of both publications support our findings.…”
Section: Discussionmentioning
confidence: 89%
“…Next, a compression fracture of the Th12 vertebra (CF) was performed. Thoracolumbar Spine Injury Classification System (AO classification) is divided into 3 injury subgroups: A (compression injuries), B (tension band injuries) and C (translational injuries in any axis) which are successively divided into subtypes [ 15 ]. Moreover, literature data show that approximately 50% of all fractures are compression fractures of the Th12 vertebra [ 1 3 ], where only the vertebral body is damaged without damage to the posterior column.…”
Section: Methodsmentioning
confidence: 99%